AIRBORNE PARTICULATE MATTER POLLUTION GENERATED BY PHOSPHATE EXPORT AT THE PORT OF ANNABA - Mekti, Z.; Boutemedjet А.; Sekiou О.; Berdoudi, S.; Chaib, A.; Kouider, F.; Rahmani, A.; Benselhoub, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
For several decades, airborne particulate matter (PM) pollution has become one of the major concerns of policymakers across the globe, due to its adverse effects on climate, human health, environment and various socio-economic sectors. The process of phosphate export in bulk is one of the main source generating air pollutants, such as PM emissions of different shapes, concentrations and particle sizes, which can cause respiratory diseases. The objective of this work is to determine the dust level generated by the processes of unloading, storage and loading of phosphate in bulk to ships, by the company of the port installation at the port of Annaba (East of Algeria). The PM measurement campaign was carried out according to the NF X 43-014. It was performed on 08 sampling points located at the port of Annaba and in a periphery with a radius of up to 2.3 km. The recorded results show very high levels of dust in 05 samples series largely exceeding the acceptable threshold (1000 mg/m²/day). The level of heavy metals in dust was evaluated by the analysis of Atomic Absorption Spectrometry. EDAX analysis showed that the phosphate PM have an angular morphology elongated particles and hook-shaped.